Pengaruh Kualitas Sistem Informasi Sumber Daya Manusia, Pelatihan dan Pengembangan terhadap Kinerja Karyawan melalui Disiplin Kerja pada PT. Era Mulia Abadi Sejahtera - Sholikah, Hesti; Ardianto, Yusaq Tomo; Prasetya, Dwi Arman (Universitas Merdeka Malang, 2022)
The aims of this study is to analyze the effect of the quality of human resource information systems, training and development, and work discipline on employee performance. The technique of analysis uses a linear regression analysis. The population of this sample was 116 workers. The findings have shown the quality of human resource information systems and training and development will enhance the discipline of work. This ensures that the quality of human resource systems accompanied by the seriousness of the workers in training and development will strengthen work discipline. Therefore, the quality of human resource information systems and training & development will enhance the employee performance. Moreover, the work discipline mediates the impact of the quality of human resources information system as well as training and development on employee performance.